# Solve Using the Square Root Property 24x^2-12x=0 24×2-12x=0
Factor 12x out of 24×2-12x.
Factor 12x out of 24×2.
12x(2x)-12x=0
Factor 12x out of -12x.
12x(2x)+12x(-1)=0
Factor 12x out of 12x(2x)+12x(-1).
12x(2x-1)=0
12x(2x-1)=0
Divide each term by 12 and simplify.
Divide each term in 12x(2x-1)=0 by 12.
12x(2x-1)12=012
Simplify 12x(2x-1)12.
Simplify terms.
Cancel the common factor of 12.
Cancel the common factor.
12x(2x-1)12=012
Divide x(2x-1) by 1.
x(2x-1)=012
x(2x-1)=012
Apply the distributive property.
x(2x)+x⋅-1=012
Reorder.
Rewrite using the commutative property of multiplication.
2x⋅x+x⋅-1=012
Move -1 to the left of x.
2x⋅x-1⋅x=012
2x⋅x-1⋅x=012
2x⋅x-1⋅x=012
Simplify each term.
Multiply x by x by adding the exponents.
Move x.
2(x⋅x)-1⋅x=012
Multiply x by x.
2×2-1⋅x=012
2×2-1⋅x=012
Rewrite -1x as -x.
2×2-x=012
2×2-x=012
2×2-x=012
Divide 0 by 12.
2×2-x=0
2×2-x=0
Factor x out of 2×2-x.
Factor x out of 2×2.
x(2x)-x=0
Factor x out of -x.
x(2x)+x⋅-1=0
Factor x out of x(2x)+x⋅-1.
x(2x-1)=0
x(2x-1)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
x=0
2x-1=0
Set the first factor equal to 0.
x=0
Set the next factor equal to 0 and solve.
Set the next factor equal to 0.
2x-1=0
Add 1 to both sides of the equation.
2x=1
Divide each term by 2 and simplify.
Divide each term in 2x=1 by 2.
2×2=12
Cancel the common factor of 2.
Cancel the common factor.
2×2=12
Divide x by 1.
x=12
x=12
x=12
x=12
The final solution is all the values that make x(2x-1)=0 true.
x=0,12
Solve Using the Square Root Property 24x^2-12x=0     